AI-powered speech device as a tool for neuropsychological assessment of an older adult population: A preliminary study - Daniela E. Aguilar Ramirez; Lukas Grasse; Scott Stone; Matthew Tata; Claudia L.R. Gonzalez (Acta Psychologica)
As the older adult population continues to expand, the demands on the healthcare system intensifies, necessitating the development of technologies that effectively accommodate the requirements of older adults. While Artificial Intelligence (AI) systems hold promise as a solution, they have not been designed to accommodate the sensory and cognitive changes typical of aging individuals. The current study investigates the use of an AI-powered communication device for the assessment of neuropsychological tests to an older adult population. Twenty-four (twelve females) older adult participants completed three memory tasks using the AI device: logical memory, poem recall, and the backward and sequencing digit span tests. Significant negative correlations were found between the age of the participants and performance on the Logical memory and digit span tests. The AI device effectively identified age-related memory changes comparable to those observed with human administrators. Implementing this technology in healthcare offers several advantages: alleviating healthcare professionals' workload, improving standard of care by reaching underserved populations, and facilitating continuous screening for early identification of prodromal stages of neurodegenerative diseases.